PENGARUH PENGGUNAAN AI POE UNTUK MEMBANTU PEMBELAJARAN BAHASA INGGRIS - Adella Nur Khasanah; Daviq Rizal (Universitas Negeri Surabaya, 2025)
This study explores the use of AI Poe in enhancing English language learning, focusing on its impact on productivity, user confidence, challenges faced, and its future potential. Through a survey involving 100 respondents, the research highlights that AI Poe is predominantly used by young, educated individuals for educational purposes. The majority of participants reported that AI Poe is highly beneficial in improving their productivity and confidence in academic and professional settings. However, challenges related to usability, accuracy, and tool responsiveness were also identified. Despite these challenges, the respondents expressed strong beliefs in the future impact of AI Poe, both in work and education, and a high willingness to recommend it to others. The study concludes that AI Poe is a promising tool for language learners, but continuous development and refinement are necessary to meet the evolving needs of diverse users.